2006
DOI: 10.1002/jssc.200600048
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Klason lignins by reversed-phase high-performance liquid chromatography using wide-pore octadecylsilica and stepwise gradients of dimethylformamide in water

Abstract: RP-HPLC using stepwise gradients of N,N-dimethylformamide (DMF) in a phosphate-buffered (pH 3.00) aqueous mobile phase and a wide-pore (30 nm) octadecylsilica column has been applied to the analysis of a variety of lignins--organocell lignin, dioxane lignin, Björkman lignin, and Klason lignins from both softwoods and hardwoods, respectively, in order to demonstrate the usefulness of the approach for their characterization. Tandem combination of spectrophotometric diode array detection and fluorimetric detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The ProZap C 18 column with 40% DMF resulted in high back-pressure (>25 MPa) [52] and could not be used. Poor separation was noted even at a lower flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…The ProZap C 18 column with 40% DMF resulted in high back-pressure (>25 MPa) [52] and could not be used. Poor separation was noted even at a lower flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic activity of tertiary amines closely parallels to the base strength of the amines except when steric hindrance becomes pronounced. [48][49][50] In our studies, catalytic effects could even be observed inuencing the PU coating quality, in particular the homogeneity of the coating surface. In general, tertiary amines inuence the crosslinking density thereby also improving the coating stability, an effect also observed by other groups.…”
Section: Lignin-derived Polyurethanes (Lpu)mentioning
confidence: 99%
“…While chromatographic methods are often employed in conjunction with wet chemical methodology, a few instrumental developments probing lignin structure are worth discussing [44,[52][53][54][55][56]. Aromatic lignin compounds, derived from naturally and artificially aged paper were identified using capillary zone electrophoresis (CZE) [52].…”
Section: Chromatographymentioning
confidence: 99%
“…Despite the preferential reaction of p-CAT with SA, higher S lignin content was not detected in plants with elevated p-CA content. Isolated lignins from various hardand softwood feedstocks were partitioned and characterized using a reverse phase-HPLC instrument equipped with a wide-pore octadecylsilica column [53]. The authors determined that a 10-step gradient using N,N-dimethylformamide and fluorimetric detection enabled well-defined lignin peaks.…”
Section: Chromatographymentioning
confidence: 99%
See 1 more Smart Citation